Demography, growth and robots in advanced and emerging economies - Matteo Lanzafame (Fondazione Eni Enrico Mattei (FEEM), 2021)
This paper provides estimates of the impact of demographic change on labor productivity growth, relying on annual data over 1961-2018 for a panel f 90 advanced and emerging economies. We find that increases in both the young and old population shares have significantly negative effects on labor productivity growth, working via various channels – including physical and human capital accumulation. Splitting the analysis for advanced and emerging economies shows that population ageing has a greater effect on emerging economies than on advanced economies. Extending the benchmark model to include a proxy for the robotization of production, we find evidence indicating that automation reduces the negative effects unfavorable demographic change – in particular, population aging-on labor productivity.
Keywords: C33; J11; O40; 330; Demographic Change; Labor Productivity; Robots